Primary structure of the catalytic subunit of human DNA polymerase delta and chromosomal location of the gene. - Chung, D W (1991)
The catalytic subunit (Mr approximately 124,000) of human DNA polymerase delta has been cloned by PCR using poly(A)+ RNA from HepG2 cells and primers designed from the amino acid sequence of regions highly conserved between bovine and yeast DNA polymerase delta. The human cDNA was 3443 nucleotides in length and coded for a polypeptide of 1107 amino acids. The enzyme was 94% identical to bovine DNA polymerase delta and contained the numerous highly conserved regions previously observed in the bovine and yeast enzymes. The human enzyme also contained two putative zinc-finger domains in the carboxyl end of the molecule, as well as a putative nuclear localization signal at the amino-terminal end. The gene coding for human DNA polymerase delta was localized to chromosome 19.